2007
DOI: 10.1681/asn.2007010125
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–Phenotype Correlations in Autosomal Dominant and Autosomal Recessive Polycystic Kidney Disease

Abstract: The phenotypes that are associated with the common forms of polycystic kidney disease (PKD)-autosomal dominant (ADPKD) and autosomal recessive (ARPKD)-are highly variable in penetrance. This is in terms of severity of renal disease, which can range from neonatal death to adequate function into old age, characteristics of the liver disease, and other extrarenal manifestations in ADPKD. Influences of the germline mutation are at the genic and allelic levels, but intrafamilial variability indicates that genetic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
120
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 72 publications
(62 reference statements)
4
120
0
3
Order By: Relevance
“…5,6 The genotype-phenotype correlation is not completely understood in ADPKD. 7 Linkage studies identified two disease-causing genes, Polycystic Kidney Disease 1 protein (PKD1; Chr.16p13.3; NG_ 008617.1) and Polycystic Kidney Disease 2 protein (PKD2; Chr.4q22.1; NG_008604.1). 8,9 Molecular screening may confirm the clinical diagnosis with a mutation frequency of 76% PKD1 and 13% PKD2.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The genotype-phenotype correlation is not completely understood in ADPKD. 7 Linkage studies identified two disease-causing genes, Polycystic Kidney Disease 1 protein (PKD1; Chr.16p13.3; NG_ 008617.1) and Polycystic Kidney Disease 2 protein (PKD2; Chr.4q22.1; NG_008604.1). 8,9 Molecular screening may confirm the clinical diagnosis with a mutation frequency of 76% PKD1 and 13% PKD2.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several other extrarenal manifestations occur less frequently but can be observed at any age and disease stage [2,4,5]. The variability of organ involvement in ARPKD is not completely understood [6,7]; however, different combinations of mutations in the fibrocystin gene PKHD1 and its resulting changes in the fibrocystin/polyductin protein structure may at least partially explain the phenotypic variance [7,8]. It is widely recognized and corroborated by intrafamilial clinical variability among affected siblings that resulting ARPKD phenotypes frequently cannot be simply explained on the basis of the PKHD1 genotype.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized and corroborated by intrafamilial clinical variability among affected siblings that resulting ARPKD phenotypes frequently cannot be simply explained on the basis of the PKHD1 genotype. Phenotypes may also depend on the background of other genes, combinations of mutations or diseasemodifying genes, epigenetic factors, hormonal effects, and environmental influences [6,7,9]. However, severe phenotypes, such as neonatal demise, are more often associated with chain-terminating, truncating PKHD1 mutations than with moderate phenotypes, and the presence of two chainterminating mutations invariably results in perinatal lethality [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic kidney disease is broadly divided into 2 forms, autosomal recessive polycystic kidney disease (ARPKD) and autosomal dominant polycystic kidney disease (ADPKD) [4][5][6][7][8]. The diseases are caused by mutation either in PKD1 (85%) or PKD2 (15%) and PKD3 (rare) genes [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%